PEMBELAJARAN ROUNDTABLE MENGGUNAKAN MEDIA PUZZLE DALAM PEMBELAJARAN MAHAROH QIRO’AH DI KELAS VII MTS. MIFTAHUL ULUM TONGGOWA KECAMATANPRIGEN KABUPATEN PASURUAN - Lailatur Rif'ah; Syaifullah (Fakultas Agama Islam Universitas Yudharta Pasuruan, 2021)
In a learning process, one of the important components of success that must be considered is the use and utilization of learning media. Improving the quality of teaching and learning processes and outcomes in an institution and at every level of education needs to be realized optimally so that human resources (HR) can be fulfilled so that they are able to compete to support national development in our country, Indonesia in particular and the whole world in general. With such great expectations, we should increase student activity in the learning process. For this reason, the use of Puzzle media is an effort to make learning more interesting so that it can help students understand the material more easily, train students' creativity, concentration and focus on subject matter, can teach students to work in teams (please help) and develop knowledge according to the topic of the lesson. by presenting examples in class. The objectives of this study are: 1- to determine the use of media in learning Arabic at MTs Miftahul Ulum Tonggowa 2- to determine the results of the influence of student learning on Arabic subjects at MTs Miftahul Ulum Tonggowa between before and after using Puzzle media. For this reason, in achieving the above objectives, in this study the researchers used a qualitative method (qualitative method) withe any of type of research using tests, direct observation, interviews and documentation. The data obtained were analyzed using participatory observation techniques, namely combining the data obtained from the research process. By using this method, the researchers saw an increase in students' enthusiasm for learning Arabic.